EFFECT OF ASHITABA (Angelica keiskei) IN LOWERING BLOOD GLUCOSE LEVELS IN MICE (Mus musculus L.) - Musparlin Halid; Sri Rahmawati (Indonesian Journal for Health Sciences, 2023)
Ashitaba has been traditionally used for its potential health benefits and is generally considered safe when consumed as part of a balanced diet, it's essential to approach its usage with caution and consult a healthcare professional before starting any new supplement regimen. The study was conducted to determine the activity of ashitaba leaf extract (Angelica keiskei) on reducing blood glucose levels in alloxan-induced mice. This research method is pre and post-control group design. Twenty-five mice were divided into five treatment groups. Group I (negative control) was given PEG 4000, group II (positive control) was given glibenclamide, and groups III, IV, and V were given Ashitaba leaf extract at 300, 600, and 1200 mg/kg BW doses. The study results were divided into 2 groups, namely groups of mice with Pre-Diabetes Mellitus and groups of mice with Diabetes Mellitus. The 1200 mg/kg BW dose of Ashitaba (Angelica keiskei) leaf extract has the highest activity in reducing blood glucose levels in the group of mice with Pre-Diabetes Mellitus, while the 600 mg/kg BW dose of Ashitaba (Angelica keiskei) leaf extract has the highest activity in reducing blood glucose levels in mice with Diabetes Mellitus. Thus, Ashitaba leaf extract can reduce blood glucose in mice